Computer-Guided Implant Surgery in Fresh Extraction Sockets and Immediate Loading of a Full Arch Restoration: A 2-Year Follow-Up Study of 14 Consecutively Treated Patients - M. Daas; A. Assaf; K. Dada; J. Makzoumé (Hindawi Limited, 2015)
Statement of Problem. Low scientific evidence is identified in the literature for combining implant placement in fresh extraction sockets with immediate function. Moreover, the few studies available on immediate implants in postextraction sites supporting immediate full-arch rehabilitation clearly lack comprehensive protocols. Purpose. The purpose of this study is to report outcomes of a comprehensive protocol using CAD-CAM technology for surgical planning and fabrication of a surgical template and to demonstrate that immediate function can be easily performed with immediate implants in postextraction sites supporting full-arch rehabilitation. Material and Methods. 14 subjects were consecutively rehabilitated (13 maxillae and 1 mandible) with 99 implants supporting full-arch fixed prostheses followed between 6 and 24 months (mean of 16 months). Outcome measures were prosthesis and implant success, biologic and prosthetic complications, pain, oedema evaluation, and radiographic marginal bone levels at surgery and then at 6, 12, 18, and 24 months. Data were analyzed with descriptive statistics. Results. The overall cumulative implant survival rate at mean follow-up time of 16 months was 97.97%. The average marginal bone loss was 0,9 mm. Conclusions. Within the limitations of this study, the results validate this treatment modality for full-arch rehabilitations with predictable outcomes and high survival rate after 2 years.